RESULTS OF TREATMENT OF OPEN FRACTURES IN PATIENTS WITH POLYTRAUMA IN A REGIONAL TRAUMA SYSTEM - A. N. BLAZHENKO; S. N. KURINNYI; M. L. MUKHANOV; M. YU. AGEEV; A. V. GORBUNOV; E. A. SHATSKAYA; K. N. SAVITSKAYA (Кубанский научный медицинский вестник, 2018)
Aim. To analyze options for treatment tactics for open fractures of bones, implemented in a regional trauma system in theKrasnodar Territory.Materials and methods. Retrospective analysis includes the results of treatment of 82 patients with polytrauma and severe open fractures of the shin bones aged from 18 to 60 years, of whom 23 in unstable or critical condition, hospitalized in 2016-2017 in the Scientific Research Institution – S.V. Ochapovsky Regional Clinical Hospital № 1.Results. Treatment tactics for patients with severe polytrauma and open fractures type IIIA and B according to the classification of Gustilo-Andersen adopted in trauma center of level I, reduces the total number of infectious complications to 9,09% for fractures of type III A and 53,84% of IIIB fractures compared to option treatment strategies adopted in trauma centres II, III where the level of infection reaches 58,06% fractures type III A and 93,75% of IIIB fractures. The typical mistakes made in primary surgical treatment in patients with polytrauma and severe open fractures were revealed: incomplete revision of the wound with leaving foreign bodies, non-viable soft tissues, unstable fixation of the fracture with the help of a skeletal traction system, incomplete external fixation of the fracture with a device or plaster bandage, suturing of the wound with relaxing skin incisions during soft tissue swelling, absence of drains or passive drainage of the open fracture.Conclusion. The usage of primary surgical treatment in a reduced volume, with the application of VAC-dressings, in patients with polytrauma and severe open fractures of the limb bones can reduce the overall incidence of infectious complications.